Response and early recovery following 4 September 2010 and 22 February 2011 Canterbury earthquakes: Societal resilience and the role of governance. (December 2015) - Mamula-Seadon, Ljubica; McLean, Ian
Abstract: This paper examines changes to governance introduced during the response and the recovery following 4 September 2010 and 22 February 2011 Canterbury earthquakes and discusses how post-disaster "time compression" can highlight the strengths and weaknesses of disaster management processes and governance frameworks. The paper focuses on some of the fundamental principles of sustainable risk management and societal resilience, namely integrated planning and creation of empowering settings for affected communities, and analyses the effectiveness of the newly introduced arrangements in respect to those principles. The paper concludes that large scale disasters challenge decentralised, integrated planning environments based on bottom-up approaches. Disasters can overwhelm local capacity whilst putting intense pressure on central government to deliver. This may generate creative solutions for known weaknesses, but at the same time the need for immediacy can jeopardise practice that fosters resilience. The paper concludes that the question of central control versus local empowerment remains as yet unanswered in New Zealand. Understanding the implications of large scale disasters on devolved, bottom-up approaches based on integrated planning merits further study. In particular, understanding the mechanisms for integration and empowerment of local communities is essential for effective recovery and resilience.